(3GdecJaj aj Gdhba hGdEHJOGs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s
(3ChdgG (B:s
(3bGd GdEeGe CHh YeQh YKeGf Hf SYjO GdMeO ddg GdefaQO HGdbOQI GdeJhLO HGdcHQjGA CeG HYO agPG cJGH Gdhba GdJGe hGdhba GdcGai hGdMSf ai cJGH Gddg YR hLd s
(3BNQgG (B:s
(3Yf GSeGA HfJ CHj HcQ , bGdJ (B: (3ef Udi GdLeYI Ke bQC bd gh Gddg CMO hGdeYhPJjf , MaX Ch cai ef eLdSg Pdc Zdi eKdg Je cJGH GdecJai ai Gdhba hGdEHJOG HMeO Gddg hYhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3ai ChdgG ChQGb bdjdI HNW MOjKs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B254 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B653s
Keywords: (3GdbQGAGJ hGdJLhjOs